PEMBINAAN KOMPETENSI DOSEN JURUSAN PENDIDIKAN LUAR SEKOLAH MELALUI COACHING CLINIC PENULISAN ARTIKEL ILMIAH - Fauzi Kurniawan; Nurlaila Nurlaila; Faber Simorangkir (JURNAL KELUARGA SEHAT SEJAHTERA, 2018)
ABSTRACTThe type of this study is quantitative research with a pre-test and post test design. The data were collected through questionnaire method. Hypothesis test was done by using t-test to test the existence of difference and Anova test to see the improvement of ability of the research sample that is to know the difference of ability (knowledge and skill) of PLS lecturer in producing scientific articles published in accredited national journals and reputable international journals through coaching clinic. The population in this study is all lecturers majoring outside of FIP Unimed Education. Sampling was done randomly by looking at the lecturers' teaching activity, research and scientific articles writing from their research results to the journal. Based on the statistical results, it can be seen that the minimum pre-test value were obtained 70,00 by LSL Lecturer before joining coaching clinic and the maximum value was 73,00. The average value obtained was 71.25 with a standard deviation value was 1.21. While the post test value obtained after the PLS lecturer joined the coaching clinic starting from the material in the classroom to the speker’s guidance, then the minimum value obtained was 74.00 and the maximum value was 85.00. The average value obtained was 80.41 with 3.11 standard deviation. While at the calculation of t Test were obtained a statistical value that t-calculate = -12.61; while t Table, ie tdf = 11; Α = 0.05 = 2.20. This means that t> tdf = 29; Α = 0.05. Thus, it can be said that these two average values statistically are significantly different. It means that in the post-test, the average value obtained by PLS Lecturer after attending the coaching clinic was higher than the average score obtained by the lecturer before attending the coaching clinic. Therefore, it can be argued that in addition to improving the ability in writing scientific articles, the implementation of coaching clinic can help PLS Lecturers to improve thinking, analyzing, writing and reviewing skill thus it can increase the quantity and quality of writing scientific articles to be published in the accredited journal. Keywords: coaching clinic, scientific articles, competence